2011
DOI: 10.1017/s0963548311000137
|View full text |Cite
|
Sign up to set email alerts
|

Incidences in Three Dimensions and Distinct Distances in the Plane

Abstract: We first describe a reduction from the problem of lower-bounding the number of distinct distances determined by a set S of s points in the plane to an incidence problem between points and a certain class of helices (or parabolas) in three dimensions. We offer conjectures involving the new setup, but are still unable to fully resolve them.Instead, we adapt the recent new algebraic analysis technique of Guth and Katz [9], as further developed by Elekes et al. [6], to obtain sharp bounds on the number of incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 22 publications
1
82
0
Order By: Relevance
“…, which, although vacuous for |S| ≤ p, beats the claim of Theorem 12 already for |S| ≥ p 30 29 . The key quantity behind the latter estimate is the energy-type non-pinned version of equation (14), that is the variable s in the right-hand side of the three-variable equation in (14) turns into the fourth variable s ′ ∈ S. For the minimum number of pinned distances for |S| ≥ p 15 14 in F p one can use estimate (6), which yields the existence of Ω Sketch of proof of Theorem 12. Consider equation (16), assuming that at most ǫ|S| points of S are collinear, for some absolute ǫ > 0, or there is nothing to prove.…”
Section: On Distinct Distances a Well-known Question Of Erdős About mentioning
confidence: 99%
“…, which, although vacuous for |S| ≤ p, beats the claim of Theorem 12 already for |S| ≥ p 30 29 . The key quantity behind the latter estimate is the energy-type non-pinned version of equation (14), that is the variable s in the right-hand side of the three-variable equation in (14) turns into the fourth variable s ′ ∈ S. For the minimum number of pinned distances for |S| ≥ p 15 14 in F p one can use estimate (6), which yields the existence of Ω Sketch of proof of Theorem 12. Consider equation (16), assuming that at most ǫ|S| points of S are collinear, for some absolute ǫ > 0, or there is nothing to prove.…”
Section: On Distinct Distances a Well-known Question Of Erdős About mentioning
confidence: 99%
“…The proof relies on a group action argument. The idea of using group action argument to attack distance problem dates back to the solution to the Erdős distance problem ( [8], [12]). On Falconer distance problem, authors in [11] observed that Mattila's integral (1.1) can be interpreted in terms of Haar measures on O(d), that is,…”
mentioning
confidence: 99%
“…First, if (S ac , (b, d)) ∈ G, then |ac| = |bd|. This is easy to derive from equations (3) and (4): expand the products and subtract (4) from (3). Also see Figure 4.…”
Section: Lemmamentioning
confidence: 99%
“…The same paper includes the conjecture that the strongest possible bound is 1 The term additive energy, referring to the number of quadruples (a, b, c, d) in some underlying set of numbers such that a + b = c + d, was coined by Tao and Vu [8]. Starting with the work of Elekes and Sharir [3], and Guth and Katz [6] on the distinct distance problem, the strategy of using geometric incidence bounds to obtain upper bounds on analogously defined energies has become indispensable in the study of questions about the number of distinct equivalent subsets. |Q| = O(Kn 2 ).…”
Section: Introductionmentioning
confidence: 99%